Seeking a common path: structuring multistakeholder dialogue on agricultural biotechnology in Africa - von Grebmer, Klaus; Omamo, Steven Were (International Food Policy Research Institute, 2006)
This paper analyzes an ongoing effort by national, regional, and international partners to raise awareness, promote dialogue, and catalyze consensus-building mechanisms among stakeholder groups on the role of biotechnology in agricultural development and food security in southern Africa. Stakeholders include public bodies, the private sector, and civil society. The paper argues that while responsible adoption of agricultural biotechnology promises significant gains to the countries of southern Africa, governments must clarify its specific role, improve policies for its application, and assess the place of biotechnology in broader development strategies. The issues that surround the introduction, creation, and application of agricultural biotechnology in southern Africa are complex, and the passions behind them are strong. The best chance of building consensus lies in bringing different views to the table for deliberation and information sharing, thus starting a process of collaborative planning, implementation, and evaluation of various activities. Deepening the dialogue and involving more parties has many challenges. Strong conflicts among members are to be expected, and there is a risk of dissolution of the dialogue process as a result of these conflicts and other factors such as lack of interest and shortage of resources. If stakeholders focus on the process, these obstacles can be overcome. Building trust and commitment among the members, maintaining communication, exchanging knowledge, and being open to revision of old views will help the dialogue continue and will ultimately make it more productive.